2021
DOI: 10.3389/fdgth.2021.600333
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Conversational Agent to Support the Self-Management of Adults and Young Adults With Sickle Cell Disease: Usability and Usefulness Study

Abstract: Sickle cell disease (SCD) is the most common genetic blood disorder in the world and affects millions of people. With aging, patients encounter an increasing number of comorbidities that can be acute, chronic, and potentially lethal (e.g., pain, multiple organ damages, lung disease). Comprehensive and preventive care for adults with SCD faces disparities (e.g., shortage of well-trained providers). Consequently, many patients do not receive adequate treatment, as outlined by evidence-based guidelines, and suffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 72 publications
0
40
0
Order By: Relevance
“…The application of two filters resulted as follows: first, 22 articles were published in 2020; second, and after selecting health topic as a domain area, 11 articles emerged as a final result. In the end, this material was spread across these different Frontier Journals categories: digital health ( N = 7) ( 20 26 ); public health ( N = 2) ( 27 , 28 ); and psychiatry ( N = 2) ( 29 , 30 ). All 11 titles were analyzed through a double review discussion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of two filters resulted as follows: first, 22 articles were published in 2020; second, and after selecting health topic as a domain area, 11 articles emerged as a final result. In the end, this material was spread across these different Frontier Journals categories: digital health ( N = 7) ( 20 26 ); public health ( N = 2) ( 27 , 28 ); and psychiatry ( N = 2) ( 29 , 30 ). All 11 titles were analyzed through a double review discussion.…”
Section: Resultsmentioning
confidence: 99%
“…Issom et al ( 20 )—This study met the inclusion criteria of “articles related to any chronic disease” defined in the second search phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of these factors have also been found to play a role in previous work. Issom et al (2021) , for instance, saw that the empathy expressed by a conversational agent was particularly appreciated, and de Graaf, Allouch & Van Dijk (2015) observed that the expression of human-like emotions by a social robot was perceived as important. Expressing empathy has also been shown to help a virtual agent to form and maintain a relationship with a user ( Bickmore et al, 2005 ), which can support behavior change ( Zhang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Expressing empathy has also been shown to help a virtual agent to form and maintain a relationship with a user ( Bickmore et al, 2005 ), which can support behavior change ( Zhang et al, 2020 ). In addition, Issom et al (2021) observed that the anonymous nature of conversing with a conversational agent was valued. Regarding situational awareness, both de Graaf, Allouch & Van Dijk (2015) and Issom et al (2021) obtained similar findings in that participants preferred the social robot to understand more than just pre-programmed commands and that users of conversational agents requested more flexible answer choices.…”
Section: Resultsmentioning
confidence: 99%